Kekuatan Email sebagai Alat Bukti dalam Proses Persidangan Perkara Perdata - Cokorda Agung Cahaya Darmadi; I Made Minggu Widyantara; Made Sukaryati Karma (Warmadewa Press, 2022)
With the rapid development of technology and telecommunications, it is easier for someone to send letters via e-mail. This is because the use of e-mail is considered cheap and fast. The purpose of this study is to reveal the proof of the use of e-mail based on the ITE Law and how the power of e-mail in the trial process is related to Article 1866 of the Civil Code. This study uses the type of normative legal research. The raw materials used in this research are primary, secondary, and tertiary. There are two results from this study. First, proof of e-mail as evidence based on the trial of civil cases, the evidence in the form of e-mail can be used in trials regarding the legal aspects of the application of e-mail in enforcing the law. act which then has an impact on the law. Second, the strength of e-mail evidence as a process of proof in the trial when it is associated with Article 164 HIR regarding valid evidence.